The Impact of a Ballet and Modern Dance Performance on Heart Rate Variability in Collegiate Dancers - Rohan Edmonds; Meaghan Wood; Patricia Fehling; Sarah DiPasquale (MDPI AG, 2018)
Heart rate (HR) variability (HRV) is a useful tool for assessing cardiac autonomic function and identifying potential readiness to perform in athletic populations, but has yet to be investigated in dance populations. As such, HRV may be able to provide valuable insight into the preparedness of dancers and the demands of performance in a collegiate dance population. 29 female dancers were monitored leading up to and following a dance performance. Analysis of HRV focused on the square root of the mean squared differences of the successive RR intervals (RMSSD). A one-way ANOVA, with Bonferroni post-hoc, paired with magnitude-based-inferences (MBI) with effect sizes (ES) were used to analyze changes during the Winter Dance Concert, while the Recovery-Stress Questionnaire for Athletes (REST-Q Sport) measured the frequency of stress of dancers. When compared to baseline (69.8 ± 1.7 bpm), mean (HR) was increased at both pre-show recordings (76.5 ± 2.1 bpm and 75.6 ± 1.8 bpm). In contrast, RMSSD was significantly diminished (p < 0.05) at both pre-show recordings (40.6 ± 28.4 ms and 40.5 ± 21.8 ms) as compared to baseline (70.3 ± 38.4 ms). Dancers reported increased (p < 0.05) self-efficacy before the second show and at 36 h post-concert. As expected, Dance Exposure (DE) increased significantly (p < 0.05), while Academic Exposure (AE) was similar, during the week leading up to the dance concert. The results suggest dancers responded to concert dance performances similarly to other athletic populations approaching intense competition by exhibiting decreased parasympathetic activity prior to the dance performances, which returned to baseline values 36 h after their performances. Given the increase in self-efficacy, these fluctuations may indicate a readiness to a performance comparable to athletes.